DAMPAK KEBIJAKAN REKLAMASI PANTAI MEGAMAS BAGI MASYARAKAT NELAYAN DI KECAMATAN WENANG KELURAHAN WENANG SELATAN KOTA MANADO - BENYAMIN BANGA PADANG; MASJE PANGKEY; ALDEN LALOMA (JURNAL ADMINISTRASI PUBLIK, 2022)
This study was conducted to determine the impact of the Megamas beach reclamation policy on the fishingcommunity in the sub-district of the authority of the southern authority of the city of Manado. This studyuses descriptive qualitative research methods. There are several dimensions of policy impact, namely theexpected and unexpected policy impact, the impact of the policy on conditions or groups outside the policygoals or objectives, the impact of the policy on the current state of affairs or conditions in the future, theimpact of direct costs, costs incurred spent to finance public policy programs, the impact of indirect costsdue to public policies that make some people suffer the consequences. Based on the research results,coastal reclamation policy has an impact beyond the target of the policy. The beach reclamation policywhich aims to build a business area actually makes fishing communities have to bear the impact of thepolicies carried out. The coastal reclamation policy has affected the economy of the surroundingcommunity, especially the fishing community whose income has decreased because the fishing communityhas to go far to sea to find fish.Keywords: Policy Impact, Beach Reclamation, Fishing Community.